Application of Earned Value Analysis to Determine Labour Productivity and Suggestions for Corrective Actions to Reduce Decreased Labour Productivity - Harsha Abhichandani, Amruta Chavan, Neha Deshmukh, Ranjitsing Gaikwad (Mathematical Statistician and Engineering Applications, 2022)
Employing project management, one may boost both material and human resource production. The project performance assessment method known as EVM (Earned Value Management) has been modified for use in project management. The analysis compares the number of hours scheduled, actual, and earned. The scheduling, monitoring, and forecasting of projects are the topics of the current study. In addition, it covers the key factors that determine how Earned Value Analysis is determined for schedule and cost management of civil construction projects. About 33% to 50% of the total project cost is thought to be the labour expenses in the construction business. It is important to understand and study the effects of labour because it is more inconsistent and unpredictable than other project-cost components.